SOSIALISASI PEMANFAATAN SAMPAH ORGANIK DAN PELAKSANAAN KEGIATAN PENGHIJAUAN DI DESA PANENJOAN KECAMATAN CARENANG - Popi Dayurni; Andreas Canra Irana Simanjuntak; Najri Hudayana; Erika Mustikasari; Rizka Putri Andiri; Muhamad Aburizal Rahmadhani; Elsa Ananda Sophian; Pahimatul Hidayah (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Penenjoan Village is in Carenang, Serang Regency, Banten. The problem faced by this village is the poor distribution of waste in the Panenjoan Village area where garbage collectors rarely pick up their trash while they produce quite a lot of waste. Therefore, the activity of utilizing organic waste is expected to be able to reduce the level of concern of residents about the accumulation of waste. This activity can also add value to the use of waste and shift the habits of residents who usually throw away garbage immediately. After this, they can first choose waste that can be reprocessed into a more useful form, such as fertilizer. In addition, in the dry season, the environment in Penenjoan Village tends to be hot and dusty. . Deciduous vegetation gives an arid and uncomfortable impression around the village environment. The effort to create a clean, green and healthy environment begins with cleaning the environment, planting trees, and awareness to care for and preserve the environment. Reforestation is one of the important activities carried out in reducing the impact of the environmental crisis